PRODUK OLAHAN SELAI BUAH PALA PADA INDUSTRI RUMAH TANGGA DI DESA KASIMBAR BARAT - Nadjib, Amalia Noviyanty; Adrianton; Yusran; Nurlina; Sitti Marwiah (JURNAL PENGABDIAN FARMASI DAN SAINS, 2024)
West Kasimbar Village is a key nutmeg production center with significant potential for the development of value-added processed products. However, the village's home industries face various challenges, such as a lack of knowledge about effective processing technology, unmet product quality standards, and limited market access. This community service program is designed to provide comprehensive solutions to these issues, focusing on improving the quality and diversification of products, particularly by processing nutmeg into nutmeg jam. The goals of this program are to analyze the potential of nutmeg farmers and home industries, offer alternative high-value nutmeg products, and explore the prospects for developing nutmeg-based flagship commodities through diversification efforts that empower women in West Kasimbar Village. The training and counseling methods used in this diversification program involve lectures combined with technology transfer to ensure understanding of nutmeg processing procedures. A demonstration of nutmeg jam production will be conducted as one of the promising value-added products. Nutmeg jam, as a derivative product, holds economic value for home industries, especially for women in West Kasimbar Village, by providing support in mastering processing technology and ensuring the sustainability of these home industries. Kata kunci: Diversifikasi, industri rumah tangga, selai pala, teknologi pengolahan.